Functional support of the first part of competitive distance in cyclic sports with endurance ability: rowing materials - Pengcheng, G.; Xianglin, K.; Rusanova, O.; Diachenko, A.; Weilong, W. (Journal of Physical Education and Sport, 2020)
Purpose: Given the differences in the duration of a distance, and as a result, differences in the duration and intensity of the first half of a distance, the variants of the initial part of the competitive activity in cyclic endurance kinds of sports are analyzed. Participants. The study included the leading rowers of the province - members and candidates for Shandong provincial rowing team. Total - 28 man athletes at the age from 18 to 23 years. Studies were conducted in the water sports centre of Shandong Province (China) during the competition period. Results: Achieving of the maximum power of work in the segment is connected with the use of special modes of starting activity realization at which the formation of the most generalized and specialized properties of endurance of the rowers with respect to the starting and other segments of competitive activity happens. These properties include the development and maintenance of the reactive properties of organism under conditions of fatigue, as well as the development and maintenance of the mechanisms of fatigue overcoming, which include, in turn, reactions of compensation of non-metabolic and metabolic acidosis.The implementation of such conditions is to a great extent concerned with the layout of forces oriented at the relatively long - 120 s- starting acceleration. However, the individual assessment of the structure of functional support of the beginning of the race, in particular, the evaluation of the dynamics of the mentioned above mechanisms of performance, especially the kinetics of CRS reactions, could make a substantial correction in the duration and intensity of the starting segment of the race